MHD flow and heat transfer of a jeffrey fluid over a stretching sheet with viscous dissipation - Ahmad, Kartini; Ishak, Anuar (Institute Mathematical Sciences, Universiti Putra Malaysia, 2016)
The steady two-dimensional magnetohydrodynamic (MHD) boundary layer flow and heat transfer of a Jeffrey fluid over a stretched sheet in the presence of viscous dissipation is studied. The horizontal sheet is considered to have a non-isothermal temperature. The governing equations that govern the fluid flow and heat transfer are in the form of partial differential equations, which are then reduced to a set of non-linear ordinary differential equations by a similarity transformation. The resulting differential equations are solved numerically using an implicit finite-difference scheme. The effects of Deborah number β, Eckert number, magnetic parameter and Prandtl number on the flow and heat transfer characteristics are investigated.